2022
DOI: 10.1039/d2bm00186a
|View full text |Cite
|
Sign up to set email alerts
|

The osteogenic response to chirality-patterned surface potential distribution of CFO/P(VDF-TrFE) membranes

Abstract: Piezoelectric poly(vinylidene fluoride-trifluoroethylene) has demonstrated an ability to promote osteogenesis, and the biomaterials with a chirality-patterned topological surface could enhance cellular osteogenic differentiation. In this work, we created a chirality-patterned...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Dong et al created a chiral geometric topology with micron-scale ups and downs to promote the distribution of cell adhesion states according to the designed pattern, which enhanced the mechanical conduction of the cytoskeleton and finally regulated the osteogenic function of cells. At the same time, our previous studies have shown that the distribution of macroscopic surface potential chirality can also effectively improve the osteogenic ability of cells . However, for the current study, the mechanism by which pattern modulation of surface potential affects macrophage polarization and immune responses remains unclear.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Dong et al created a chiral geometric topology with micron-scale ups and downs to promote the distribution of cell adhesion states according to the designed pattern, which enhanced the mechanical conduction of the cytoskeleton and finally regulated the osteogenic function of cells. At the same time, our previous studies have shown that the distribution of macroscopic surface potential chirality can also effectively improve the osteogenic ability of cells . However, for the current study, the mechanism by which pattern modulation of surface potential affects macrophage polarization and immune responses remains unclear.…”
Section: Introductionmentioning
confidence: 80%
“…The electroactive films were prepared as reported in previous studies. 12 The magnetic particles (10 wt % (CFO/P(VDF-TrFE)) were dispersed in N,N-dimethylformamide (DMF, Sinopharm Chemical Reagent Co. Ltd) and ultrasonically dispersed for 6 h. P(VDF-TrFE) powder was added and stirred for 2 h. Films were prepared on the chirality-patterned ITO substrate by the solution casting method. After heat treatment at 210 °C for 60 min, the CFO/ P(VDF-TrFE) films were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance its ferroelectric and piezoelectric attributes, researchers (Nunes-Pereira et al, 2015) introduced the trifluoroethylene monomer (TrFE) into PVDF, resulting in the copolymer Poly(vinylidene fluoridetrifluoroethylene) (P(VDF-TrFE)), which exhibit improved charge accumulation and storage capabilities, enabling the acquisition of a permanent surface potential. P(VDF-TrFE) is capable of carrying surface charge and has been demonstrated to promote osteogenesis in MSCs in vitro (Luo et al, 2022;Zhang et al, 2022), enhance bone repair in vivo (Gimenes et al, 2019;Zhang et al, 2022), and facilitate macrophage polarization (Dai et al, 2021). The application of an external power source through ITO planar microelectrodes can impart a continuous electrical stimulation to cells or tissues, thereby influencing their morphology and function.…”
Section: Introductionmentioning
confidence: 99%
“…P(VDF-TrFE) is capable of carrying surface charge and has been demonstrated to promote osteogenesis in MSCs in vitro ( Luo et al, 2022 ; Zhang et al, 2022 ), enhance bone repair in vivo ( Gimenes et al, 2019 ; Zhang et al, 2022 ), and facilitate macrophage polarization ( Dai et al, 2021 ). The application of an external power source through ITO planar microelectrodes can impart a continuous electrical stimulation to cells or tissues, thereby influencing their morphology and function.…”
Section: Introductionmentioning
confidence: 99%